Root growth behavior in Delbergia sissooo plantation developed in degraded land-A case study - Agrawal, Rashmi; Oja, B.M.; Pandey, S.; Dixit, B.; Wani, Mohd. Rafi; Sharma, S.B. (Indian Journal of Agroforestry, 2020)
A Case study was conducted to collect information on the root growth behavior of Dalbergia sissoo in three different girth classes (15- 25 cm, 25- 35 cm, 35- 45 cm) and seasonal variation in three distinct seasons viz., summer, rainy and winter under plantation developed at degraded land. The distribution of root biomass was detected from various depth classes (0-15 cm, 15- 30 cm, 30- 45 cm and 45- 60 cm) and radial distances (50 cm, 100 cm and 150 cm). The sampling of tree has been done randomly. Root distribution study was carried out with Monolith method which involves the partial excavation of soil sample to represent the whole part of the rooting volume of the tree. Among the three seasons of observations, rainy season recorded the maximum rooting intensity, root density and root biomass followed by winter and summer.The results revealed that increase in distance and depth led to decrease in root activity by reduced rooting intensity, root density and root biomass. Maximum rooting intensity of 496.84 m-2 and maximum root density of 0.0231 cm cm-3 were registered in the upper soil category (50 cm distance of 0-15 cm soil depth i.e. D1d1) in 35-45 cm girth class trees during rainy season. Significantly higher root biomass of 541.77 g M-3 was recorded in 50 cm distance of 15-30 cm soil depth i.e. D2d2 category in 35-45 cm girth class trees during rainy season.